AVIAN INFLUENZA A VIRUS SURVEILLANCE IN RESERVOIR DOMESTIC DUCKS (Anas platyrhynchos domesticus) IN MAIDUGURI METROPOLITAN COMMUNITY OF NORTH-EASTERN NIGERIA: A NEED FOR ONE-HEALTH APPROACH (FUDMA JOURNAL OF SCIENCES, 2024)
The domestic ducks (Anas platyrhynchos domesticus) are natural reservoir hosts of avian influenza A virus (AIV) and have since remained significant in the ecology and epidemiology of the virus globally.  Continued local surveillance for AIV in this specie is critical to assessing the risks of potential spreading to domestic poultry, other animal species, and zoonotic transmission to humans. In this study, we investigate the status of AIV in domestic waterfowls in Maiduguri metropolis. Twenty-eight cloacal and oropharyngeal swab samples were collected from apparently healthy domestic ducks from November to December 2021 in Bulumkutu (n=2), Giwa Barracks (n=5), Kasuwan Shanu (n=4), Maimalari Barracks (n=5), Mairi (n=5), Premier (n=2) and Shehuri (n=4). Samples were screened for AIV using the real-time RT-PCR molecular assay. A total prevalence of 60.7% (CI: 41.99 –77.32) was recorded. Prevalence based on locations was higher in Bulumkutu 100% (CI:22.36 - 100), Kasuwan Shanu 100% (CI: 22.36 - 100), and Shehuri 100% (CI:47.29 - 100). In Maimalari Barracks and Mairi, prevalence of 60% (18.24 – 92.65) each was recorded respectively. While samples from Giwa Barracks and Gomari had a prevalence of 40% (CI: 7.346 – 81.76) and 33.3% (1.667 – 86.8). AIV was not detected in samples from premier (0%). The result of this study revealed the status of AIV in domestic ducks in Maiduguri metropolis. Thus, this early warning call the need  for AIV prevention and control in the region and using the one-health approach to access the zoonotic potential of the virus in the domestic ducks...
Keywords: Domestic Ducks; Influenza A; Maiduguri Metropolis; Reservoir Surveillance; One-Health